2020
DOI: 10.1007/s12274-020-2656-5
|View full text |Cite
|
Sign up to set email alerts
|

Shape anisotropic Fe3O4 nanotubes for efficient microwave absorption

Abstract: Although Fe 3 O 4 particles have exhibited excellent microwave absorbing capacity and widely used in practical application due to the synergistic effect of magnetic loss and dielectric loss, their applications are still limited for the required high mass fraction in absorbers. To overcome this problem, the development of Fe 3 O 4 materials with low dimensional structures is necessary. In this study, the shape anisotropic Fe 3 O 4 nanotubes (NTs) with low mass ratios were applied to realize efficient microwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…It's clear that the maximum reflection loss (RL) value of Co/PCNF moves to the low frequency band with a decrease in thickness, where the show in Fig. 9 f. This phenomenon can be mainly explained by the theory of quarter-wavelength, which can be expressed by the following equation 51 , 53 :
Figure 9 ( a ) Reflection loss (RL) curves for CoNPs, ( b ) Reflection loss (RL) curves for PCNF, ( c ) S1, ( d ) S2 and ( e ) S3 with different thickness in the frequency range of 2–18 GHz, ( f ) RL values of Co/PCNF at “matching thickness” (tm) in 2.00–18.00 GHz.
where c is the velocity of light.…”
Section: Resultsmentioning
confidence: 93%
“…It's clear that the maximum reflection loss (RL) value of Co/PCNF moves to the low frequency band with a decrease in thickness, where the show in Fig. 9 f. This phenomenon can be mainly explained by the theory of quarter-wavelength, which can be expressed by the following equation 51 , 53 :
Figure 9 ( a ) Reflection loss (RL) curves for CoNPs, ( b ) Reflection loss (RL) curves for PCNF, ( c ) S1, ( d ) S2 and ( e ) S3 with different thickness in the frequency range of 2–18 GHz, ( f ) RL values of Co/PCNF at “matching thickness” (tm) in 2.00–18.00 GHz.
where c is the velocity of light.…”
Section: Resultsmentioning
confidence: 93%
“…9 Traditional ferrite materials possess exclusive features of strong saturation magnetization, high complex permeability as well as being of low cost, which have been extensively applied in the eld of microwave absorption. 10,11 Ferrosoferric oxide (Fe 3 O 4 ) as the simplest ferromagnetic substance has been widely used in dye degradation, 12 biomedical applications, 13 hydrogen storage, 14 energy storage devices, 15 electromagnetic absorbers, 16 etc. Especially in the domain of microwave absorption, natural resonance and eddy-current effect reveal unexceptionable magnetic loss in the high-frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…reported that compared with Fe 3 O 4 particles, Fe 3 O 4 nanotubes have significant multiple resonances with stronger coercivity, which are beneficial to microwave absorption. [ 8 ] Yang and co‐works found that iron nanowires have higher permeability and better EMW absorption performance than iron nanoparticles. [ 9 ] However, to achieve excellent EMW absorption performance, the loading of 1D magnetic metal materials in matrix is usually higher than 30 wt%, which is not conducive to the lightweight development of EMW absorbing materials.…”
Section: Introductionmentioning
confidence: 99%